POPULATION-CENTERED DEVELOPMENT THROUGH IPBK INTEGRATION IN REGIONAL PLANNING - Mubarak Husni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Regional development planning requires an evidence-based approach that utilizes population dynamics as the basis for establishing policy priorities. The Population-Based Development Index (IPBK) was developed as a composite indicator to measure the linkages between development and population structure and needs. However, this study found that the IPBK has not been systematically integrated into the RPJPD (Regional Medium-Term Development Plan), RPJMD (Renstra OPD), RKPD (Regional Work Plan), and budgeting documents. This policy paper employs a qualitative-descriptive methodology, utilizing policy analysis techniques grounded in regulatory evaluations, scrutiny of regional planning documents, and a Results-Based Management (RBM) framework to identify deficiencies in indicator integration and performance cascading mechanisms. The discussion reveals three main problems: the absence of binding regional regulations, the lack of a cascading mechanism for the IPBK to regional apparatus indicators, and weak cross-sectoral oversight and utilization of the SIPD (Regional Development Planning Agency). Consequently, the IPBK has not yet functioned as an outcome indicator that controls the direction of development. The main recommendation is the institutionalization of the IPBK through a Regional Head Regulation that mandates the integration of indicators, the development of cascading technical SOPs, and the establishment of a cross-regional government agency (OPD) oversight forum to ensure more measurable, accountable, and population-centered regional development.